2016
DOI: 10.1016/j.appet.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

‘Emotional’ does not even start to cover it: Generalization of overeating in emotional eaters

Abstract: Based on recent studies indicating that emotional eating is not the clearly defined problem it is often 33 thought to be, the present study investigated whether emotional eaters overeat merely in response to 34 negative emotional cues, or to other cues as well. It was hypothesized that emotional eaters would 35 overeat after a variety of food cues, not limited to negative emotions. Participants took part in four 36 conditions (negative mood manipulation, positive mood manipulation, food exposure and a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
0
40
1
4
Order By: Relevance
“…Werthmann et al (2014) induced a negative or a neutral mood in their participants, but did not find an effect of self-reported emotional eating status on food intake. In a recent study in which memory recall was paired with personal music, Bongers et al (2016) found a moderate correlation between self-reported emotional eating and food intake in both a negative and positive mood. In addition, they found increased food intake when feeling both negative and positive in emotional eaters compared to non-emotional eaters.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Werthmann et al (2014) induced a negative or a neutral mood in their participants, but did not find an effect of self-reported emotional eating status on food intake. In a recent study in which memory recall was paired with personal music, Bongers et al (2016) found a moderate correlation between self-reported emotional eating and food intake in both a negative and positive mood. In addition, they found increased food intake when feeling both negative and positive in emotional eaters compared to non-emotional eaters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, a recent study (Bongers et al, 2016), reasoned that emotional eaters could be better defined based on their actual food intake when in a negative mood: participants who ate the most after negative mood induction were considered emotional eaters. In counterbalanced order, the participants underwent a negative mood induction, a positive mood induction, food cue exposure, and a control procedure (all within subjects).…”
Section: What Do High Scores On Emotional Eating Scales Really Reflect?mentioning
confidence: 99%
“…Emotional eating is a response to negative emotions: a "tendency to overeat in response to negative emotions, such as anxiety or irritability" [1] (p. 106). More recently, researchers view it as a response to both negative and positive mood [2][3][4]. Emotional eating in eating disorders may reflect general difficulties with emotion regulation [5].…”
Section: Introductionmentioning
confidence: 99%
“…This disparity in either overeating or under-eating in the general population has been observed in clinical samples, and recent studies suggest that, besides obesity, EE could be involved in the entire spectrum of eating disorders: not only in binge eating episodes as in bulimia nervosa (BN) or binge eating disorder, but also in binge-purging and restrictive anorexia nervosa (Ricca et al, 2009, 2012). There is also growing evidence showing that positive emotions are considered to be an underestimated risk factor for food intake and overeating (Bongers et al, 2013a,b, 2016; Evers et al, 2013), but little is known about their effects on eating behaviors compared to those documented for negative emotions (Macht, 2008). However, recent studies suggest that eating in response to negative and to positive emotions could refer to different constructs (van Strien et al, 2013) and that only the desire to eat in response to negative emotions would be an ‘obese’ eating style (van Strien et al, 2016).…”
Section: Introductionmentioning
confidence: 99%